A study of the nuclear structure of even-even Te isotopes in the Interacting Boson Model framework - Theodoropoulos, Vissarion; Aikaterini Zyriliou; Polytimos Vasileiou; Theo J. Mertzimekis (HNPS Advances in Nuclear Physics, 2024)
The even-even tellurium isotopes (Z=52) are part of a region beyond the closed proton shell at Ζ=50 and are generally considered to exhibit vibrational-like properties. These properties are investigated in the present work using the the Interacting Boson Model (IBM-1) framework to estimate the energy levels, transition quadrupole moments and the reduced transition probabilities B(E2) of the even-even 104-140Te isotopes. In addition, the deformation parameters β2 and γ have been calculated providing a useful visualization of the nuclear shapes in these isotopes. The results have been compared to available adopted data and used as estimates for unavailable ones.